Plastic for diaphragmal hernia - I. I. Rosenfeld (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Aim. The article discusses the results of a study using a patented method of two-layer laparoscopic repair of large and giant hiatal hernias using a biocarbon implant in comparison with other surgical techniques.Materials and methods. 716 patients were divided into 3 study groups based on the area of the size of the esophageal hernia defect: group I (314 patients) – with small (less than 5 cm2) and medium (5–10 cm2) hiatal hernias, that is, up to 10 cm2, which hernioplasty was performed only by the method of posterior cruraphy; group II (323 patients) – with large hernias 10–20 cm2: subgroup 1 (92 patients) underwent posterior cruraphy, subgroup 2 (231 patients) – alloplasty. Depending on the alloplasty technique, subgroup 2, in turn, was divided: subgroup A (89 people) – hernioplasty with a polypropylene implant and subgroup B (142 people) – hernioplasty with a medical biocarbon construction. Study group III (79 patients) – patients with giant diaphragmatic hernias of more than 20 cm2 using alloplasty: subgroup A (29 people) – hernioplasty with a polypropylene implant and subgroup B (50 patients) – alloplasty with a medical biocarbon construction.Results. When comparing group I with subgroup 1 of group II, the following results were obtained. Statistically significant differences were found in the degrees and types of diaphragmatic hernias. The average age of patients and statistical differences for it were insignificant. When comparing subgroup 1 with subgroup 2 of group II, statistically insignificant differences were found in the degrees and types of hiatal hernias. The difference in the average age of patients was also statistically insignificant. The difference in the average age of patients was also statistically insignificant. When comparing subgroup A with subgroup B of group II, statistically insignificant differences were found among themselves in the degrees and types of hiatal hernias. When comparing subgroup 2 of group II with group III, the difference turned out to be statistically significant in the distribution of patients by types and degrees of diaphragmatic hernias. When comparing subgroup A with subgroup B of group III by degrees and types of hiatal hernias, statistically insignificant differences were revealed.Conclusion. Posterior cruraphia in small and medium diaphragmatic hernias had significant statistical differences in types and degrees compared to that in large hernias, as well as in the average area of the hernial defect. Posterior cruraphia with hernioplasty in large hiatal hernias did not differ statistically significantly according to any of the criteria. Plastic surgery with a polypropylene implant with alloplasty of a biocarbon implant for large hernias did not differ significantly according to any of the criteria. Hernioplasty for large hiatal hernias, when compared with giant hernias, differed significantly only in the degree and type, as well as in the area of the hernial defect. «Onlay» plastic surgery with a polypropylene implant with alloplasty of biocarbon structures for giant hernias did not differ significantly according to any of the criteria, except for gender distribution, which did not have significant fundamental significance, which made it possible to make a more correct comparison of the results of surgical interventions in these research subgroups.